Dentinal growth layer counts of captive, known-age, mother and daughter belugas (Delphinapterus leucas): confirming two growth layer groups (GLG/2) per year; consequences for recovery and management - Brodie, P.; Haulena, M. (J. Cetacean Res. Manage., 2023)
Captive mother and daughter belugas (Delphinapterus leucas) of Hudson Bay origin died at the Vancouver Aquarium, in November 2016, aged 29.25 and 21.25 years. Aurora, captured at age three and captive since 1990, gave birth to Qila in 1995. Age and histories being known, the focus of this study was on total number of tooth growth layer groups (GLGs) present; one (GLG/1) or two (GLG/2) per year. Teeth from Aurora indicated two growth layers per year (GLG/2) during pre-capture and captivity. Qila deposited GLG/2 throughout her captive life. Clearly an assumption of GLG/1 over GLG/2 doubles the duration of all life stages, including lifespan and age at attainment of sexual maturity. Arguments for GLG/1 have been based on inferences (e.g. from fallout of bomb radio carbon) from adults of unknown age and history, while those for GLG/2 are based on the projection of direct observations from newborn, known-age young to 21 and 29 year-old adults from captivity. Use of radiocarbon is ingenious but such analyses have not been rigorously tested on marine mammals and the sensitivity to necessary correction factors not addressed. The new information from this study contradicts the GLG/1 hypothesis in that such an assumption would place Aurora’s birth at the 1958 peak fallout of bomb radiocarbon (14C) yet she was born 29 years later in 1987, while the birth of her daughter Qila would pre-date the birth of her mother by 13 years. This paper re-assesses three studies that assigned GLG/1 based ages to older adults using GLG/2 and concludes that their supposed births would also pre-date the realistic births of their own mothers plus as many as two previous generations. Proponents of GLG/1 have overestimated the ages of previous calves-at-capture by 200–800%. Given the growth pattern in teeth of these 21 year and 29 year old female belugas, with increasingly finer dentine GLGs deposited as the pulp tissue diminishes, it is difficult to envisage the GLG/1 tooth structures of those assumed to be 60–80 years; none are as yet available. An holistic analysis using direct observations and cross-referenced parameters does not substantiate GLG/1which implies a 40% reduction of the intrinsic rate of natural increase; as a consequence, overestimating historical population size as well as recovery target population and the predicted date of recovery in Cumberland Sound.